2022
DOI: 10.1111/gcb.16238
|View full text |Cite
|
Sign up to set email alerts
|

Daytime warming triggers tree growth decline in the Northern Hemisphere

Abstract: Global warming has been linked to declines in tree growth. However, it is unclear how the asymmetry in daytime and nighttime warming influences this response. Here, we use 2947 residual tree‐ring width chronologies covering 32 species at 2493 sites, between 1901 and 2018, across the Northern Hemisphere, to analyze the effects of daytime and nighttime temperatures, precipitation, and drought stress on the radial growth of trees. We show that drought stress was primarily triggered by daytime rather than nighttim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 79 publications
2
11
1
Order By: Relevance
“…However, the contributions of daytime and nighttime temperatures to explain the variations of treeline recruitment were uneven (Figure 2), suggesting that the sensitivity of recruitment in treelines to daytime and nighttime warming was systematically heterogeneous. This implied the asymmetric effects of daytime and nighttime warming on recruitment in treelines, being in line with a recent global-scale research which found that daytime and nighttime warming, especially during the warmest months, had opposite effects on tree growth in warm regions (Tao et al, 2022).…”
Section: Sitessupporting
confidence: 90%
See 2 more Smart Citations
“…However, the contributions of daytime and nighttime temperatures to explain the variations of treeline recruitment were uneven (Figure 2), suggesting that the sensitivity of recruitment in treelines to daytime and nighttime warming was systematically heterogeneous. This implied the asymmetric effects of daytime and nighttime warming on recruitment in treelines, being in line with a recent global-scale research which found that daytime and nighttime warming, especially during the warmest months, had opposite effects on tree growth in warm regions (Tao et al, 2022).…”
Section: Sitessupporting
confidence: 90%
“…In addition, the standardized precipitation-evapotranspiration index (SPEI), which could deal with drought events at multiple timescales by considering the effects of temperature, potential evapotranspiration, and precipitation (Vicente-Serrano et al, 2010) (Tao et al, 2022) and thus were used to examine the effects of climate warming on drought.…”
Section: Climate Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In dry temperate regions, where summer T max approaches or even exceeds the optimum temperature for plant photosynthesis (Huang et al, 2019), T max was more closely correlated with drought‐related indicators than T min (Figures 8–10), suggesting that daytime warming is the primary driver of drought stress across the NH (Tao et al, 2022). Rising T max intensifies water stress by increasing VPD (Figures 8e and 9e) and PET (Figures 8h and 9h) and reducing soil water (Figures 8b and 9b; Ciais et al, 2005; Niu et al, 2008; Vicente‐Serrano et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tree growth mainly occurs at night, while photosynthesis and transpiration occur in the daytime, which indicates that diurnal temperature ranges and atmospheric water demand are critical to the growth response ( Zweifel et al., 2021 ). Daytime warming can reduce tree growth ( Tao et al., 2022 ); when the diurnal temperature ranges are small, the net growth of trees is large ( Zhang et al., 2022 ). Therefore, higher BIO2 is not conducive to plant growth, and appropriate BIO3 is conducive to the expansion of the plant habitat.…”
Section: Discussionmentioning
confidence: 99%